“For her own safety and the good of society at large”: Eugenics, Sterilization, and Anglo-American Transnationalism in Newfoundland, 1928-1934 - Connor, J. T. H. (Acadiensis, 2019)
From 1928 to 1934, about half of the two dozen women who were surgically sterilized while under the care of American doctors working with the International Grenfell Association (IGA) in St. Anthony, Newfoundland, were sterilized because they were deemed to be mentally unfit or substandard. These sterilizations coincided with rising concern about feebleminded persons and eugenic and legislative solutions across the United States, the British Empire, and beyond, but Newfoundland did not develop a eugenic movement nor did it enact laws to sanction surgical sterilization. What happened in St. Anthony was a result of the otherwise beneficial “Americanization” of the IGA.